Vigil : Hong Kong on the brink - Wasserstrom, Jeffrey N (Columbia Global Reports, 2020)
"On the frontlines of the battle for democracy in China The rise of Hong Kong is the story of a miraculous post-War boom, when Chinese refugees flocked to a small British colony, and, in less than fifty years, transformed it into one of the great financial centers of the world. The unraveling of Hong Kong, on the other hand, shatters the grand illusion of China ever having the intention of allowing democratic norms to take root inside its borders. Hong Kong's people were subjects of the British Empire for more than a hundred years, and now seem destined to remain the subordinates of today's greatest rising power. But although we are witnessing the death of Hong Kong as we know it, this is also the story of the biggest challenge to China's authoritarianism in 30 years. A small group of activists, who are passionately committed to defending the special qualities of a home they love, are fighting against Beijing's crafty efforts to bring the city into its fold-of making it a centerpiece of its "Greater Bay Area" megalopolis. Jeffrey Wasserstrom, one of America's leading China specialists, draws on his many visits to the city, and knowledge of the history of repression and resistance, to help us understand the deep roots and the broad significance of the events we see unfolding day by day in Hong Kong. The result is a riveting tale of tragedy but also heroism-one of the great David-versus-Goliath battles of our time, pitting determined street protesters against the intransigence of Xi Jinping, the most ambitious leader of China since the days of Mao"--